FTIR and UV-Visible Spectral Study on Normal and Jaundice Blood Samples - Gunasekaran, S.; Uthra, D. (Asian Journal of Chemistry, 2010)
Passing from normal tissue to pathological tissue, cellular biochemistry changes. From a diagnostic and therapeutic point of view, it is fundamental to study the physical and chemical changes occurring in tissues and cells due to disease. Spectroscopy has received quite a lot of attention not only for understanding the biological nature of the disease, but also for the diagnosis of the disease in recent years. FTIR spectroscopy technique is employed to study the spectral differences in the serum of healthy and jaundice affected subjects. Based on the differences in the spectral signatures, four intensity ratio parameters are used in this study. The set of samples that have been subjected to FTIR study were subjected to UVvisible spectral studies too. The results from the latter one are used to ascertain the former results. Student's t-test has been used to anlayse the set of data obtained and to characterize the sera as healthy and diseased.